Enhancing Home Security in North-East of Nigeria using Home Automation - Dr. Karim Usman; Ike Innocent (International Journal of Engineering and Management Research, 2022)
Home automation plays a vital and essential role in modern era because of its usability and flexibility in using it at different places with high precision which will save cost and time by decreasing human stress. The main purpose of this technology is to control the household equipment’s like, door, fan, AC, light etc. automatically. This research work has concentrated information on Home Automation and Security System using Arduino, GSM and how we can control home appliances using Android Application. Whenever a person will enter into the house then the count of the number of persons entering in the house will be incremented, in Home Automation mode appliances will be turned on whereas in security light will be turned on along with the alarm. The count of the number of persons entering the house is also outputted on the LCD screen. In Home Automation mode when the room will become empty i.e. the count of persons reduces to zero then the appliances will be turned off making the system power efficient. The owner can control his home appliances by using an android application present in his mobile phone which will reduce the human stress. At the same time if anyone enters while security mode is on a SMS will be sent to house owner’s mobile phone which will indicate the presence of a person inside the house. The alarm can be turned off using SMS or Android application.